Analisis Pengaruh Kepercayaan dan Harga Terhadap Loyalitas Pelanggan Dimediasi Kepuasan Pada PT. Telkomsel di Kota Kediri - Laely, Nur (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2016)
To know clearly about customer satisfaction and loyalty at PT. Telkomsel in Kediri Town of East Java, this research focused on the models of customer’s satisfaction and loyalty increase based on customer trust, and product prices. From the testing results of the model in this research, by using random sampling, structural equation modeling (SEM) analysis, and the assistance of software Amos 20, on 150 respondents, it was able to explain the relationship between trust, price, and customer satisfaction on the customer loyalty in PT. Telkomsel in Kediri Town of East Java. In this research, it was obtained a strong influence of customer trust and satisfaction, amounting to 0.429, and a strong influence between customer satisfaction and loyalty, that is of 0.233, it showed that, with the rising customer trust, it will increase customer satisfaction, which in turn raise the loyalty of PT. Telkomsel customers. In this study, it also found the negative effects of price and customer satisfaction, amounting to -0.089, and the strong influence of negative between price and loyalty of customers, that is of -0.406, this case indicated that, with the rising of product prices, it will lower customer satisfaction, which further lowers the loyalty of PT. Telkomsel customers. Keywords: trust, prices, satisfaction, and customer loyalty